Photo-inactivation of Bacillus endospores: inter-specific variability of inactivation efficiency - Silva, Raquel Nunes da (2019)
The aims of this work were to (a) evaluate the susceptibility of endospores of Bacillus cereus, B. licheniformis, B. sphaericus and B. subtilis to photodynamic inactivation using a tricationic porphyrin as photosensitizer, (b) assess the efficiency of adsorption of the photosensitizer in endospore material as a determinant of the susceptibility of endospores of different Bacillus species to photo-inactivation, (c) determine the value of B. cereus as a model organism for studies of antimicrobial photodynamic inactivation of bacterial endospores. The results of irradiation experiments with endospores of four species of Bacillus showed that B. cereus was the only species for which efficient endospore photo-inactivation (> 3 log reduction) could be achieved. Endospores of B. licheniformis, B. sphaericus and B. subtilis were virtually resistant to photo-inactivation with tricationic porphyrin. The amount of porphyrin bound to endospore material was not significantly different between species, regardless of the presence of an exosporium or exosporium-like outer layer. The sensitivity of endospores to photodynamic inactivation with a tricationic porphyrin is highly variable among different species of the genus Bacillus. The presence of an exosporium in endospores of B. cereus and B. sphaericus, or an exosporium-like glycoprotein layer in endospores of B. subtilis, did not affect the amount of bound photosensitizer and did not explain the inter-species variability in susceptibility to photodynamic inactivation. The results imply that the use of B. cereus as a more amenable surrogate of the exosporium-producing B. anthracis must be carefully considered when testing new photosensitizers for their antimicrobial photo-inactivation properties.